Prevalence of timely complementary feeding initiation and associated factors among mothers having children aged 6-24 months in rural north-central Ethiopia: Community based cross-sectional study. - Moges Wubneh Abate; Adane Birhanu Nigat; Agimasie Tigabu Demelash; Tigabu Desie Emiru; Nigusie Selomon Tibebu; Chalie Marew Tiruneh; Amsalu Belete; Tilahun Kegne Abebe; Moges Yinges Yitayew (PLoS ONE, 2022)
Background Complementary foods are defined as any solid or liquid foods other than breast milk offered to children. Timely initiation of complementary foods during infancy is necessary for growth and development. The first two years of life are important period for rapid physical, cognitive and social development that requires optimal nutrition. Currently, there is no study done in this rural community about timely initiation of complementary feeding. Objective The main aim of this study was to assess the prevalence of timely initiation of complementary feeding among mothers having children aged 6-24 months in Farta district, rural Ethiopia. Methods A community-based cross-sectional study was employed from December 2020 to February 2021 among 570 mothers by using multi-stage sampling techniques. Data were collected using a structured interviewer-administered questionnaire and entered into Epi Data 4.6 then transferred to Statistical Package for Social Science version 25 for analysis. Bivariate and multivariable logistic regression analysis with a 95% confidence interval carried out to determine the association between explanatory and the outcome variables. A P-value of < 0.05 was considered statistically significant. Results The prevalence of timely initiation of complementary feeding among mothers having children aged 6-24 months was 51.9%. Institutionaldelivery [(AOR = 2.10, 95% CI: (1.31-3.32)],Keeping livestock [(AOR = 2.21, 95% CI: (1.35, 3.65)], Postnatal follow up [(AOR = 0.60, 95% CI:(0.36, 0.77)],merchants [(AOR = 4.58; 95% CI:1.99, 10.55)], and daily labourer [(AOR = 2.88, 95% CI:(1.50-5.51)] were statistically associated with timely initiation of complementary feeding. Conclusion This finding revealed that the prevalence of timely initiation of complementary feeding is still low. Factors affecting timely initiations of complementary feeding were home delivery, unable to attend postnatal care follow-up, being housewife and farmers. All health professionals including health extension workers should give special attention to advising and counseling for mothers and their husbands about timely initiation of complementary feeding.